Ag quantum dot-SnS2 composite nano gas-sensitive material, preparation method thereof and application of Ag quantum dot-SnS2 composite nano gas-sensitive material in formamide sensor
By using Ag quantum dot-SnS2 composite nanogas sensitive material in traditional MOS gas sensors, the problem of high temperature required for traditional sensors is solved, and high sensitivity detection of formamide at room temperature is achieved, reducing power consumption and improving stability.
Patent Information
- Application Number
- CN202411741413.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional metal oxide semiconductor (MOS) gas sensors require high operating temperatures, resulting in high power consumption and safety risks, and are difficult to meet the actual formamide detection needs.
Ag quantum dot-SnS2 composite nanogas-sensitive material was prepared by a mixed process of oil phase and ultrasonic method. The sensors based on this material showed good gas-sensitive properties to formamide at room temperature.
It realizes high sensitivity detection of formamide gas at room temperature, reduces sensor power consumption, and has good reproducibility, selectivity and long-term stability.
Smart Images

Figure CN119551711A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an Ag quantum dot-SnS2 composite nanometer gas-sensitive material and a preparation method thereof and application in a formamide sensor, belonging to the technical field of semiconductor gas sensors. Background Art
[0002] Formamide (CH3NO) is a versatile organic solvent that is widely used in industrial and laboratory applications and is a precursor for the synthesis of pharmaceuticals, fertilizers, and certain types of resins. In addition, formamide stabilizes single-stranded molecules during electrophoresis and plays a key role in the generation of RNA and DNA, making it valuable in biochemical research. Despite its wide range of uses, formamide (CH3NO) poses significant occupational hazards, especially through vapor exposure. In particular, it undergoes a slow and prolonged volatilization process, similar to formaldehyde. Prolonged or excessive inhalation of formamide vapors can cause respiratory irritation, headaches, dizziness, and in severe cases, damage to the liver and kidneys. Formamide is also classified as a reproductive toxin and may affect fertility and embryonic development. In addition, formamide releases ammonia at high temperatures, which can irritate the eyes and mucous membranes upon contact. Therefore, timely and accurate detection of formamide species and concentrations is crucial in industrial, laboratory, and even domestic environments. However, most research on sensor detection has focused on similar gases such as dimethylformamide and formaldehyde.
[0003] Conventional metal oxide semiconductor (MOS) gas sensors require high operating temperatures to provide sufficient thermal energy to overcome the activation barrier, and have limitations, including high power consumption, additional safety risks, and sensor performance degradation, making it difficult to meet practical detection needs. To address these issues, constructing composite structures with excellent catalytic properties has become a promising approach to improve the detection of harmful gases by promoting the decomposition of gas molecules. Summary of the invention
[0004] The present invention provides a Ag quantum dot-SnS2 composite nanometer gas-sensitive material and a preparation method thereof and an application thereof in a formamide sensor. The present invention adopts a mixed process of an oil phase method and an ultrasonic method to prepare the Ag quantum dot-SnS2 nanometer composite gas-sensitive material, and the sensor based on the Ag quantum dot-SnS2 nanometer composite material exhibits good gas-sensitive performance to formamide at room temperature of 25°C, and has high sensitivity and good reproducibility, selectivity and long-term stability.
[0005] A Ag quantum dot-SnS2 composite nanometer gas-sensitive material, wherein the microscopic morphology of the Ag quantum dot-SnS2 composite nanometer gas-sensitive material is that the Ag quantum dots are loaded on the surface of SnS2, wherein:
[0006] The SnS2 is a flower-like structure assembled from SnS2 nanosheets with a thickness of 10 to 20 nm, and the crystal structure is a hexagonal crystal structure; the Ag quantum dots are nanoparticles composed of Ag atoms with a diameter of 5 to 15 nm.
[0007] Furthermore, the molar ratio of the Ag quantum dots to SnS2 is 1:20-100.
[0008] Another object of the present invention is to provide a method for preparing a Ag quantum dot-SnS2 composite nano gas-sensitive material, which comprises adding an Ag salt to an oil phase solvent, introducing argon gas, heating and stirring to obtain a uniform and transparent mixed solution, continuing heating to obtain a brown mixed solution, and then precipitating and washing by centrifugation to obtain Ag quantum dots; adding the Ag quantum dot solution to a SnS2 suspension, ultrasonically treating to obtain a precipitate, washing by centrifugation, and drying to obtain an Ag quantum dot-SnS2 composite nano gas-sensitive material.
[0009] Further, Ag salt is added to the oil phase solvent, argon gas is introduced, and the mixture is heated and stirred at 50-70°C for 10-30 min to obtain a uniform and transparent mixed solution; the mixed solution is heated to 160-200°C at a heating rate of 2-6°C / min and maintained for 10-30 min to obtain a brown mixed solution; then, the mixture is precipitated and washed by centrifugation to obtain Ag quantum dots; the Ag quantum dot solution is added to the SnS2 suspension, ultrasonically treated for 15-40 min to obtain a precipitate, which is washed by centrifugation and dried at 50-80°C for 12h-24h to obtain an Ag quantum dot-SnS2 composite nano-gas-sensitive material.
[0010] In the above technical solution, the mass volume ratio of the Ag salt to the oil phase solvent is 0.0075 g / mL to 0.015 g / mL.
[0011] In the above technical solution, the volume ratio of the SnS2 suspension to the Ag quantum dot solution is 10mL:50~200μL.
[0012] Furthermore, the concentration of the Ag quantum dot solution is 0.0107 g / mL to 0.0168 g / mL.
[0013] Furthermore, the concentration of the SnS2 suspension is 0.0092 g / mL to 0.0184 g / mL.
[0014] Furthermore, the solvents of the SnS2 suspension and the Ag quantum dot solution are both n-hexane.
[0015] In the above technical solution, the oil phase solvent is obtained by mixing n-octadecene, oleic acid and oleylamine and continuously stirring.
[0016] Furthermore, the volume ratio of n-octadecene, oleic acid and oleylamine is 5-10:4.5:0.5.
[0017] In the above technical solution, the Ag salt is one or more of silver acetate, silver chloride or silver nitrate.
[0018] In the above technical solution, the reagent selected for the precipitation operation is isopropanol.
[0019] In the above technical solution, the centrifugal washing condition is centrifugal washing at a rotation speed of 7000-10000 rpm for 5-10 minutes.
[0020] Another object of the present invention is to provide a formamide sensor prepared using the above-mentioned Ag quantum dot-SnS2 composite nano gas-sensitive material and a method for preparing the formamide sensor.
[0021] A formamide sensor based on Ag quantum dot-SnS2 composite nano gas sensitive material, the gas sensor is composed of an Al2O3 substrate, an Au interdigital electrode and an Ag quantum dot-SnS2 composite nano gas sensitive material film uniformly coated on the surface of the Au interdigital electrode, wherein:
[0022] The number of the Au interdigital electrodes is 4 to 12 pairs, the spacing between the Au interdigital electrodes is 50 to 150 μm, and the thickness of the Al2O3 substrate is 10 μm to 15 μm.
[0023] Furthermore, the detection range of the gas sensor for formamide gas is 50-1000 ppm, and the operating temperature is 25°C.
[0024] A method for preparing a formamide sensor based on a Ag quantum dot-SnS2 composite nano-gas-sensitive material comprises the following steps: mixing the Ag quantum dot-SnS2 composite nano-gas-sensitive material with anhydrous ethanol and grinding the mixture to obtain a slurry; using a brush to evenly apply the slurry on the surface of an Au interdigital electrode in 1 to 3 layers, and then heat treating the mixture at 40°C to 70°C for 8h to 14h to obtain a formamide sensor.
[0025] Furthermore, the mass volume ratio of the Ag quantum dot-SnS2 composite nano gas-sensitive material to anhydrous ethanol is 0.1 to 0.4 g / mL.
[0026] Beneficial effects of the present invention: The formamide sensor prepared based on the Ag quantum dot-SnS2 composite nano-gas-sensitive material has a low operating temperature and can achieve high-sensitivity detection of formamide gas at room temperature, thereby reducing the power consumption of the sensor and facilitating subsequent sensor array integration and chip processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1This is the XRD spectrum of the Ag quantum dot-SnS2 composite nano gas-sensitive material obtained in Examples 1 to 4.
[0028] Figure 2 This is a scanning electron microscope photograph of the Ag quantum dot-SnS2 composite nano gas-sensitive material obtained in Example 3.
[0029] Figure 3 The response-recovery curves of the formamide sensors obtained in Examples 1 to 4 to 100 ppm formamide at room temperature 25°C are shown.
[0030] Figure 4 This is a response reproducibility curve of the formamide sensor obtained in Examples 1 to 4 to 100 ppm formamide.
[0031] Figure 5 The following are dynamic response-recovery curves of the formamide sensors obtained in Examples 1 to 4 to different concentrations of formamide at room temperature 25°C.
[0032] Figure 6 The figure is a relationship diagram between the sensitivity of the formamide sensor obtained in Examples 1 to 4 and the formamide concentration.
[0033] Figure 7 The diagram is a selectivity diagram of the formamide sensor obtained in Example 3 to 7 different types of gases; a diagram showing the effect of humidity on the sensitivity and resistance of the sensor obtained in Example 3; and a diagram showing the long-term stability detection of the sensor obtained in Example 3. DETAILED DESCRIPTION
[0034] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0035] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0036] Example 1
[0037] A formamide sensor based on Ag quantum dots-SnS2 composite nanomaterials, specifically comprising the following production steps:
[0038] (1) Add 10 mL of n-octadecene, 4.5 mL of oleic acid and 0.5 mL of oleylamine into a flask and continue stirring to prepare a mixed oil phase solvent;
[0039] (2) adding 0.168 g of silver acetate to the above-mentioned mixed oil phase solvent, introducing argon gas into the flask, heating and stirring at 60° C. for 20 min to obtain a uniform and transparent mixed solution;
[0040] (3) heating the mixed solution obtained above to 180° C. at a heating rate of 4° C. / min and maintaining the target temperature for 20 min to obtain a brown mixed solution;
[0041] (4) using isopropanol to precipitate the brown solution obtained in step (3), and then centrifugally washing it with anhydrous ethanol at a centrifugal speed of 10000 rpm for 10 min, and finally dispersing the precipitate in 10 mL of n-hexane to obtain a Ag quantum dot (Ag QDs) solution;
[0042] (5) 92 mg of SnS2 powder was added to 10 mL of n-hexane solution and dispersed by ultrasonic treatment for 10 min to obtain a suspension; then, 50 μL of Ag QDs solution was added to the suspension and ultrasonic treatment was continued for 30 min. The obtained precipitate was washed by centrifugation with deionized water and ethanol several times, and finally dried at 60 ° C for 10 h to obtain Ag QDs-SnS2 composite nano gas-sensitive material;
[0043] (6) Weigh 15 mg of Ag QDs-SnS2 composite nano-gas-sensitive material and add it to 100 uL of anhydrous ethanol, grind it to form a uniform slurry; then use a brush to dip a small amount of the slurry and evenly apply it on the surface of the Au interdigital electrode. After the film is formed, use the brush to evenly apply it again to form two layers of sensitive material coating to obtain a gas sensor;
[0044] (7) The obtained gas sensor was heat treated at 60° C. for 10 h to increase the stability of the gas sensor, thereby obtaining a formamide sensor.
[0045] Example 2
[0046] The difference between this embodiment and embodiment 1 is that the preparation parameters of step (5) are changed as follows:
[0047] 92 mg of SnS2 powder was added to 10 mL of n-hexane solution and dispersed by ultrasonic treatment for 10 min to obtain a suspension; then, 100 μL of Ag QDs solution was added to the suspension and ultrasonic treatment was continued for 30 min. The obtained precipitate was washed by centrifugation with deionized water and ethanol several times and finally dried at 60 °C for 10 h to obtain Ag QDs-SnS2 composite nano gas-sensitive material.
[0048] Example 3
[0049] The difference between this embodiment and embodiment 1 is that the preparation parameters of step (5) are changed as follows:
[0050] 92 mg of SnS2 powder was added to 10 mL of n-hexane solution and dispersed by ultrasonic treatment for 10 min to obtain a suspension; then, 150 μL of Ag QDs solution was added to the suspension and ultrasonic treatment was continued for 30 min. The obtained precipitate was washed by centrifugation with deionized water and ethanol several times and finally dried at 60 °C for 10 h to obtain Ag QDs-SnS2 composite nano gas-sensitive material.
[0051] Example 4
[0052] The difference between this embodiment and embodiment 1 is that the preparation parameters of step (5) are changed as follows:
[0053] 92 mg of SnS2 powder was added to 10 mL of n-hexane solution and dispersed by ultrasonic treatment for 10 min to obtain a suspension; then, 200 μL of Ag QDs solution was added to the suspension and ultrasonic treatment was continued for 30 min. The obtained precipitate was washed by centrifugation with deionized water and ethanol several times and finally dried at 60 °C for 10 h to obtain Ag QDs-SnS2 composite nano gas-sensitive material.
[0054] Example 1 to 4 Results Analysis:
[0055] The XRD spectra of the Ag QDs-SnS2 composite nano gas-sensitive materials obtained in Examples 1 to 4 are as follows: Figure 1 As shown, it can be seen that: the composite nano-gas-sensitive materials obtained in Examples 1 to 4 have significant characteristic peaks of hexagonal SnS2, but no obvious characteristic peaks of Ag are found, which may be caused by the low Ag content; the enlarged spectrum shows that the (102) characteristic peak in the composite nano-gas-sensitive materials is shifted, proving the successful incorporation of Ag.
[0056] The scanning electron microscope photo of the Ag QDs-SnS2 composite nano gas-sensitive material obtained in Example 3 is shown in Figure 2 As shown, it can be seen that a large number of 5-15 nm Ag quantum dots are loaded on the SnS2 surface, and SnS2 is a flower-like structure assembled by SnS2 nanosheets with a thickness of 10-20 nm.
[0057] The response-recovery curves of the formamide sensors obtained in Examples 1 to 4 to 100 ppm formamide at room temperature 25°C are as follows: Figure 3 As shown, it can be seen that: under 25°C, the sensitivity of the sensor obtained in Example 3 to 100 ppm formamide is the highest, reaching 13.3.
[0058] The response reproducibility curves of the formamide sensors obtained in Examples 1 to 4 to 100 ppm formamide are as follows: Figure 4 As shown, it can be seen that the sensors obtained in Examples 1 to 4 all exhibit good response reproducibility to formamide.
[0059] The dynamic response-recovery curves of the formamide sensors obtained in Examples 1 to 4 to different concentrations of formamide at room temperature 25°C are as follows: Figure 5 As shown, it can be seen that: as the concentration of formamide increases, the sensitivity of the sensors obtained in Examples 1 to 4 increases accordingly, proving that they can detect formamide in a wider concentration range.
[0060] The relationship between the sensitivity of the formamide sensor obtained in Examples 1 to 4 and the formamide concentration is shown in the figure below: Figure 6 As shown, it can be seen that the sensitivity and formamide concentration of the sensors obtained in Examples 1 to 4 can be fitted with a linear equation, and the concentration value of formamide can be accurately obtained through the sensitivity value.
[0061] The selectivity, moisture resistance and long-term stability of the formamide sensor obtained in Example 3 for 7 different types of gases are as follows Figure 7 As shown, it can be seen that the sensor obtained in Example 3 exhibits the highest sensitivity and good selectivity to 100 ppm formamide; in addition, with the increase of humidity, the sensitivity and humidity of the sensor obtained in Example 3 gradually decrease, but it can still maintain relatively excellent performance at relatively high concentrations, showing good moisture resistance; the sensor obtained in Example 3 exhibits good long-term stability during the continuous test of 100 ppm formamide within 30 days.
Claims
1. An Ag quantum dot-SnS2 composite nano gas-sensitive material, characterized in that: The microscopic morphology of the Ag quantum dot-SnS2 composite nano gas-sensitive material is that the Ag quantum dots are loaded on the surface of SnS2, wherein: The SnS2 is a flower-like structure assembled from SnS2 nanosheets with a thickness of 10 to 20 nm, and the crystal structure is a hexagonal crystal structure; the Ag quantum dots are nanoparticles composed of Ag atoms with a diameter of 5 to 15 nm.
2. The material according to claim 1, characterized in that: The molar ratio of the Ag quantum dots to SnS2 is 1:20-100.
3. A method for preparing Ag quantum dot-SnS2 composite nano gas-sensitive material, characterized in that: Add Ag salt to the oil phase solvent, introduce argon gas, heat and stir to obtain a uniform and transparent mixed solution, continue heating to obtain a brown mixed solution, then precipitate, centrifuge and wash to obtain Ag quantum dots; add the Ag quantum dot solution to the SnS2 suspension, ultrasonically treat to obtain a precipitate, centrifuge and wash, and dry to obtain an Ag quantum dot-SnS2 composite nano gas-sensitive material.
4. The method according to claim 3, characterized in that: Add Ag salt to the oil phase solvent, introduce argon gas, heat and stir at 50-70°C for 10-30 minutes to obtain a uniform and transparent mixed solution; heat the mixed solution to 160-200°C at a heating rate of 2-6°C / min, maintain for 10-30 minutes to obtain a brown mixed solution; then precipitate, centrifuge and wash to obtain Ag quantum dots; add the Ag quantum dot solution to the SnS2 suspension, ultrasonically treat for 15-40 minutes to obtain a precipitate, centrifuge and wash, and dry at 50-80°C for 12h-24h to obtain an Ag quantum dot-SnS2 composite nano gas-sensitive material.
5. The method according to claim 3 or 4, characterized in that: The mass volume ratio of the Ag salt to the oil phase solvent is 0.0075g / mL~0.015g / mL; the volume ratio of the SnS2 suspension to the Ag quantum dot solution is 10mL:50~200μL, wherein the solvents of the SnS2 suspension and the Ag quantum dot solution are both n-hexane, the concentration of the Ag quantum dot solution is 0.0107g / mL~0.0168g / mL, and the concentration of the SnS2 suspension is 0.0092g / mL~0.0184g / mL.
6. The method according to claim 3 or 4, characterized in that: The oil phase solvent is obtained by mixing n-octadecene, oleic acid and oleylamine and continuously stirring, wherein the volume ratio of n-octadecene, oleic acid and oleylamine is 5-10:4.5:0.
5.
7. The method according to claim 3 or 4, characterized in that: The Ag salt is one or more of silver acetate, silver chloride or silver nitrate.
8. A formamide sensor based on Ag quantum dots-SnS2 composite nano gas sensitive material, characterized in that: The gas sensor is composed of an Al2O3 substrate, an Au interdigital electrode, and a Ag quantum dot-SnS2 composite nano gas-sensitive material film uniformly coated on the surface of the Au interdigital electrode, wherein: The number of the Au interdigital electrodes is 4 to 12 pairs, the spacing between the Au interdigital electrodes is 50 to 150 μm, and the thickness of the Al2O3 substrate is 10 μm to 15 μm.
9. The formamide sensor according to claim 9, characterized in that: The detection range of the gas sensor for formamide gas is 50-1000 ppm, and the operating temperature is 25°C.
10. A method for preparing a formamide sensor based on Ag quantum dots-SnS2 composite nano gas sensitive material, characterized in that: The Ag quantum dot-SnS2 composite nano gas-sensitive material is mixed with anhydrous ethanol and then ground to obtain a slurry; the slurry obtained above is evenly coated on the surface of the Au interdigital electrode using a brush, 1 to 3 layers are coated, and then heat-treated at 40° C. to 70° C. for 8 h to 14 h to obtain a formamide sensor, wherein: The mass volume ratio of the Ag quantum dot-SnS2 composite nano gas-sensitive material to anhydrous ethanol is 0.1-0.4 g / mL.
Citation Information
Cited By
Ag-coated SnS composite material, preparation method thereof and deep application of Ag-coated SnS composite material in field of dye molecule detection
CN121373414A
Ag@sn s composite material, preparation method thereof and deep application thereof in dye molecule detection field
CN121373414B